Design and development of high-temperature tribometer for material testing in liquid sodium environment. (2016) - Kumar, Hemant; Vijayaraghavan, S.; Albert, Shaju K.; Bhaduri, A.K.; Ray, K.K.
It is well known that high friction coefficients due to stripping of oxide films, wear and galling are common to many mating surfaces of the components of sodium cooled Fast Breeder Reactors (FBRs). Therefore, understanding tribological behaviour of various materials in liquid sodium is an important input for design of reactor components. In order to generate this information, a first-of-the-kind high-temperature Pin-on-Disc Tribometer (PODT) has been designed and fabricated for carrying out in-sodium sliding friction and wear studies in conditions simulating reactor operating conditions. The design of the tribometer incorporated consideration for convenience of operation in liquid sodium environment. The PODT system has been designed for the maximum temperature of 873 K and contact stress of 55 MPa; these parameters cover the temperature and stress levels prevailing in the operation of Indian FBRs. The appropriateness of the designed tribometer has been demonstrated with some typical experimental results.